AMERICAN MODEL OF A PLEA BARGAINING IN CRIMINAL PROCEEDINGS, WITH ACCENT ON SOME NEGATIV ASPECTS - Feješ, Ištvan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The author deals with the subject in this paper divided into introduction, five chapters and conclusion. In the introduction author gives a brief discussion on the possibilities and negative aspects of a settlement in a criminal proceeding. The first chapter deals with a brief history of origin 'plea bargaining "in judicial practice and legislation of United States. The second chapter deals with the issue of choice of form of procedure and types of settlement. The third chapter presents arguments which justify the plea bargaining. The fourth chapter is devoted to criticism of the plea bargaining. The fifth chapter deals with the evaluation of the settlement and the prospects for reform of the institute. In a brief conclusion the author raises concerns about the danger of an uncritical acceptance of the plea bargaining and its restoration in other legal systems. Author emphases that the acceptance of this institute is possible only with caution and adjustment to given legal system.Keywords: plea bargaining, American model, problems